2016 IFPRI annual report - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
Growing international commitment to sustainable development goals and notable progress in addressing food security—reflected in historically low levels of poverty and hunger in many developing countries—marked 2016. These successes are building momentum as the world seeks to end hunger and malnutrition. IFPRI is proud to contribute to progress toward these vital global goals. 2016 was the first year of implementation of the ambitious UN Sustainable Development Goals. At the ministerial-level OECD Meeting of the Committee for Agriculture, IFPRI Director General Shenggen Fan argued that improvements in the global food system will play a key role in achieving the SDGs. The 2016 Global Food Policy Report focused on reshaping the global food system to make it efficient, climate resilient, sustainable, nutrition- and health-driven, and business friendly, as means to meet these goals. The report’s signature chapter, written in collaboration with IFAD President Kanayo Nwanze, highlights the critical role that smallholders can play both in improving food security and in addressing the challenge of climate change. The 22nd United Nations Conference of the Parties (COP22) in Marrakech marked the entry into force of the Paris Agreement on climate change. At the conference, IFPRI researchers conveyed the critical role of food systems in climate change, new projections on the impact of climate change on food security, and the need to invest in climate-smart agriculture. Nutrition has also been in the spotlight. As part of the United Nations Decade of Action on Nutrition and in follow-up to the Second International Conference on Nutrition (ICN2), IFPRI participated in the International Symposium on Sustainable Food Systems for Healthy Diets and Improved Nutrition, which explored options for shaping food systems to deliver nutritious food for healthy diets. At the World Economic Forum Annual Meeting in Davos, IFPRI hosted an event on how to fill the global and national data gap on nutrition. IFPRI published the 2016 Global Nutrition Report, highlighting progress toward and obstacles to better nutrition, and Nourishing Millions: Stories of Change, which recounts success stories in improving nutrition around the world. The annual meeting and report of ReSAKSS, an Africa-wide program supporting rural development, focused on achieving a nutrition revolution in Africa.